História e fantasia: o imaginário medieval no filme: “As crônicas de Nárnia: o leão, a feiticeira e o guarda-roupa (2005)” - Sobrinho, Thais de Oliveira (Universidade Federal do Tocantins, 2023)
This research presents a film analysis on History and Fantasy: The Medieval Imaginary in the Film: The Chronicles of Narnia: The Lion, the Witch and the Wardrobe (2005). Its general objective is to identify how some elements of the medieval imaginary are reworked in this filmic work. To carry out this study, qualitative research was used based on bibliographical research. The result of the research showed the presence of the medieval imagination through forests, animals, such as the lion, fauns, cavalry weapons and titles of feudal nobility.